Methods of molecular analysis: assessing losses and gains in tumours - Roylance, R (British Medical Journal Publishing Group, 2002)
The study of chromosomal aberrations has facilitated the understanding of tumorigenesis. By applying molecular genetic techniques to regions highlighted by cytogenetic study, many genes important in tumorigenesis have been identified. This review will describe the cytogenetic and molecular cytogenetic techniques used to identify these changes. The clinical information that they can provide, including diagnostic and prognostic information, will also briefly be discussed.